Periapical cyst enucleation and simultaneous sealing of the root canal system - Lida Velazque Rojas; Alexandre Simões-Nogueira; Ilan Sampaio do Vale; Victor Tiegui Neto; Andrea Guedes Barreto Gonçales; Eduardo Sánches Gonçales (Editorial Ciencias Médicas, 2014)
Introduction: periapical cysts are the most common odontogenic cysts. Their origin is related to pulp necrosis and the consequent stimulation of epithelial rests of the periodontal ligament (Malassez). Objective: describe a clinical case of periapical cyst enucleation and simultaneous sealing of the root canal system. Case report: a female 67-year-old patient without any systemic alteration sought care for dental pain and accumulation of food in the area of the lower left molars. Clinical examination revealed extensive decay in the lower left second molar with furcation involvement and absence of vestibular volume increase without a fistula. Periapical radiography showed an extensive recurrent carious lesion in the lower left second molar and lower left first molar with endodontic treatment and presence of a radiolucent area of a sharp outline in the periapical region compatible with periapical cyst. Treatment was conducted by a multidisciplinary team, who decided to perform extraction of the lower left second molar and paraendodontic surgery with surgical enucleation and simultaneous sealing of the root canal system in the lower left first molar. Histopathological examination of the specimen removed revealed it was a periapical cyst. Radiographic follow-up conducted two years later showed complete bone repair in the affected area. Conclusions: it is concluded that the treatment described is a valid alternative for the resolution of cases in which conventional endodontics is insufficient to preserve the function and aesthetic appearance of a tooth.